\documentclass{article} \usepackage[utf8]{inputenc} \usepackage{amsmath} \usepackage{amssymb} \usepackage{amsthm} \usepackage{cancel} \setlength\parindent{0pt} \title{Numerical Analysis of DiffEq HW 1} \author{Shakil Rafi} \begin{document} \maketitle \textbf{1.1} We first need to establish a lemma: \newtheorem{lem}{Lemma} \begin{lem} $hf(t_{{n}+\frac{1}{2}},\frac{1}{2}(y(t_n)+y(t_{n+1})) = hf(t_{n+\frac{1}{2}},y(t_{n+\frac{1}{2}})) +\eta$ where $\eta$ is $\mathcal{O}(h^3)$. \end{lem} \begin{align*} ||\eta|| = h||f(t_{n+\frac{1}{2}},\frac{1}{2}(y(t_n)+y(t_{n+1})) - f(t_{n+\frac{1}{2}},y(t_{n+\frac{1}{2}})|| \\ \leq h\lambda||\frac{1}{2}(y(t_n)+y(t_{n+1})) = y(t_{n+\frac{1}{2}}) \\ \leq h\frac{\lambda}{2}|y(t_n)+y(t_n+1) - 2y(t_{n+\frac{1}{2}})|| \end{align*} Then Taylor expansion around $y(t_{n})$ gives us: \begin{align*} &||\eta|| \leq \frac{h\lambda}{2}||y+(y+hy'-2y(y+\frac{1}{2}hy')+\mathcal{O}(h^2)||\\ &= \frac{h\lambda}{2}||y+y+hy^2-2y^2-hyy'+\mathcal{O}(h^2)|| \\ &=\mathcal{O}(h^3) \end{align*} \textbf{Proving the convergence of the implicit midpoint rule}: The implicit midpoint rule is: \begin{align} y_{n+1}=y_n+hf(t_n+\frac{h}{2},\frac{1}{2}(y_n+y_{n+1})). \end{align} Substituting the exact value then gives us: \begin{align} y(t_{n+1}) = y(t_n)+hf(t_n+\frac{h}{2}, \frac{1}{2}(y(t_n)+y(t_{n+1}))+\mathcal{O}(h^2) \end{align} Following closely the proof of $(1.9)$ and $(1.4)$ we subtract $(2)$ from $(1)$, and applying the lemma to get: \begin{align*} e_{n+1} &= e_n +h(f(t_{n+\frac{1}{2}},\frac{1}{2}(y_n+y_{n+1})) -f(t_{n+\frac{1}{2}},\frac{1}{2}(y(t_n)+y(t_{n+\frac{1}{2}})) +\mathcal{O}(h^3) \\ ||e_{n+1}|| &\leq ||e_{n}|| +\frac{\lambda h}{2}(||e_{n+1}||+||e_n||)+\mathcal{O}(h^3)\\ \end{align*} We then reproduce the steps in Iserles: \begin{align*} ||e_{n+1}||-\frac{\lambda h}{2}||e_{n-1}|| &\leq ||e_n|| + \frac{\lambda h}{2}||e_n|| + \mathcal{O}(h^3) \\ ||e_{n+1}|| &\leq \bigg(\frac{1+\frac{\lambda h}{2}}{1-\frac{\lambda h}{2}}\bigg)||e_n|| + \bigg(\frac{c}{1+\frac{\lambda}{2}}\bigg) + \mathcal{O}(h^3) \\ \end{align*} And similar to Iserles we claim that: \begin{align*} ||e_n|| \leq \frac{c}{\lambda}\bigg[ \bigg(\frac{1+\frac{\lambda h}{2}}{1-\frac{\lambda h}{2}}\bigg)^n -1 \bigg]h^2 \end{align*} We will use induction to prove this step. Clearly it holds for $n=0$. Assume that the above inequality holds upto and including $n\in \mathbb{N}$, then for $n+1$ we have: \begin{align*} ||e_{n+1}|| &\leq \bigg(\frac{1+\frac{\lambda h}{2}}{1-\frac{\lambda h}{2}}\bigg)\frac{c}{\lambda}\bigg[ \bigg(\frac{1+\frac{\lambda h}{2}}{1-\frac{\lambda h}{2}}\bigg)^n -1 \bigg]h^2+ \bigg(\frac{c}{1+\frac{\lambda}{2}}\bigg) + \mathcal{O}(h^3) \\ &= \frac{c}{\lambda} \bigg[\bigg(\frac{1+\frac{\lambda h}{2}}{1-\frac{\lambda h}{2}}\bigg)^{n+1}\bigg]h^2 - \frac{c}{\lambda}\bigg(\frac{1+\frac{\lambda h}{2}}{1-\frac{\lambda h}{2}}\bigg)h^2 +\mathcal{O}(h^3) \\ &= ||e_n|| \leq \frac{c}{\lambda}\bigg[ \bigg(\frac{1+\frac{\lambda h}{2}}{1-\frac{\lambda h}{2}}\bigg)^{n+1} -1 \bigg]h^2 \end{align*} \textbf{To show that the $\theta$ method is convergent}, we define the theta method as: \begin{align*} y_{n+1} &= y_{n}+h[\theta f(t_n,y_n)+(1-\theta)f(t_{n+1},y_{n+1})] \end{align*} Whereas substituting exact solutions gives us: \begin{align*} y(t_{n+1}) y(t_n) +h[\theta f(t_n,y(t_n))+(1-\theta)f(t_{n+1},y(t_{n+1}))]+\mathcal{O}(h^3) \end{align*} Once again subtracting $(3)$ from $(4)$ gives us: \begin{align*} e_{n+1} &= e_n +h[\theta f(t_n,y_n)-\theta f(t_n,y(t_n))+(1-\theta)f(t_{n+1},y(t_{n+1}))+(1-\theta)f(t_{n+1},y(t_{n+1}))] +\mathcal{O}(h^3)\\ ||e_{n+1}|| &\leq ||e_n||+h[\theta \lambda ||e_n||+(1-\theta)\lambda ||e_{n+1}||]+\mathcal{O}(h^3) \\ ||e_{n+1}|| &\leq \bigg(\frac{1+h\theta \lambda}{1-h(1-\theta)\lambda} \bigg)||e_n||+\frac{c}{1-h(1-\theta)\lambda} +ch^3 \quad \text{for some }c \end{align*} Similar to the trapezoid method we will argue: \begin{align*} ||e_n|| \leq \frac{c}{\lambda} \bigg[ \bigg(\frac{1+h\theta \lambda}{1-h(1-\theta)\lambda} \bigg) ^n -1 \bigg] h^2 \end{align*} We argue via induction. Clearly we have that it is true for $n=0$ as at that point the exact and approximate solutions are the same. Assume now that it is true upto and including $n$. We need to prove for $n+1$: \begin{align*} ||e_{n+1}|| &\leq \bigg(\frac{1+h\theta \lambda}{1-h(1-\theta)\lambda} \bigg)||e_n||+\frac{c}{1-h(1-\theta)\lambda} +ch^3\\ ||e_{n+1}|| &\leq \bigg(\frac{1+h\theta \lambda}{1-h(1-\theta)\lambda} \bigg)\bigg(\frac{c}{\lambda} \bigg[ \bigg(\frac{1+h\theta \lambda}{1-h(1-\theta)\lambda} \bigg) ^n -1 \bigg] h^2\bigg)+\frac{c}{1-h(1-\theta)\lambda} +ch^3 \end{align*} Now observe that $\theta$ varies between $1$ and $0$. Thus $\bigg(\frac{1+h\theta \lambda}{1-h(1-\theta)\lambda} \bigg)$ varies between $1+h\lambda$ and $\frac{1}{1-h\lambda}$, both of which are bigger than one. As such we can continue and say: \begin{align*} ||e_n|| \leq \frac{c}{\lambda} \bigg[ \bigg(\frac{1+h\theta \lambda}{1-h(1-\theta)\lambda} \bigg) ^{n+1} -1 \bigg] h^2 \end{align*} \textbf{1.2a} Let $y'=Ay$, and let $e_n=y_n-y(nh)$ We want to prove using induction: \begin{align*} ||e_n||_2 \leq ||y_0||_2 \max_{\lambda \in \sigma(A)}|(1-h\lambda)^n-e^{nh\lambda}| \end{align*} But before that we make an observation: \begin{align*} e_n = y_n-y(nh) \end{align*} And since we are using Euler method, we can say: \begin{align*} y(t_{n+1}) &= y(t_n) + hy'(t) + \mathcal{O}(h^2) \\ y_{n+1} - y(t_{n-1}) &= y_n - y(nh) +h[(f(t_n,y(t_n))-f(t_n,y_n))] \end{align*} Substitution $A$ gives us: \begin{align*} e_{n+1} &= e_n+h[Ay_n - Ay(nh)]+\mathcal{O}(h^2) \\ ||e_{n+1}|| &\leq ||e_n||_2 +h\lambda ||e_n||_2+\mathcal{O}(h^2)\\ ||e_{n+1}|| &\leq ||e_n||_2(1+h\lambda) +\mathcal{O}(h^2) \end{align*} For the induction part we observe that the statement clearly holds true for $n=0$ since then we get: \begin{align*} ||e_0||_2 &\leq ||y_0||_2 \max_{\lambda \in \sigma(A)}|(1+h\lambda)^0 - e^0| \\ 0 &\leq 0 \end{align*} Using it as our base case, assume the inequality holds for upto and including $n$ the for $||e_{n+1}||$ we have: \begin{align*} ||e_{n+1}||_2 &\leq ||e_n||_2(1+h\lambda)+\mathcal{O}(h^2) \\ ||e_{n+1}||_2 &\leq ||y_0||_2 \max_{\lambda \in \sigma(A)}|(1+h\lambda)^n - e^{nh\lambda}|(1+h\lambda)+\mathcal{O}(h^2x)\\ &\leq ||y_0||_2\max_{\lambda \in \sigma(A)}|(1+h\lambda)^{n+1}-[e^{nh\lambda}+h\lambda e^{nh\lambda}]| \\ &\leq ||y_0||_2\max_{\lambda \in \sigma(A)}|(1+h\lambda)^{n+1}-e^{(n+1)h\lambda}| \end{align*} \textbf{1.2b} From the hint, we first seek to prove $1+x \leq e^x$. Let $f(x) = e^x-x-1$, then $f'(x) = e^x-1$ and $f''(x) = e^x$. There is a global minimum of $0$ and this function is concave up, and so $f(x) > 0$ over all $x$ and hence $e^x \geq 1+x$. \newline Following the hint again we seek to prove that $1+x+\frac{x^2}{2} \geq e^x$. Observe the series expansion of $e^x$ is $e^x = 1+x+\frac{x^2}{2!}+\frac{x^3}{3!}\mathcal{O}(x^3)$. Thus: \begin{align*} 1+x+\frac{x^2}{2} +\frac{x^3}{3!}+\mathcal{O}(h^4) - 1-x-\frac{x^2}{2} \\ \cancel{1}+\cancel{x}+\cancel{\frac{x^2}{2}} +\frac{x^3}{3!}+\mathcal{O}(h^4) - \cancel{1}-\cancel{x}-\cancel{\frac{x^2}{2}} \\ \frac{x^3}{3!} + \mathcal{O}(h^4) < 0 \text{ as } x\in[-1,0] \end{align*} We use a similar logic for the last part of the hint. Observe that: $(a-b)^n = \Sigma^n_{i=0}{n \choose i}a^{n-i}b^i = a^n -na^{n-1}b + ...$. So: \begin{align*} \Sigma^n_{i=1}{n \choose i}a^{n-i}b^i &- a^n+na^{n-1}b \\ \Sigma^n_{i=2}{n \choose i}a^{n-i}b^i &\geq 0 \text{ as a is close to being 1 and b is small} \end{align*} For the actual proof, let $a=e^x$ and $b=\frac{1}{2}x^2$. We then get: \begin{align*} e^{nx} - \frac{1}{2}nx^2e^{(n-1)x} &\leq (e^x-\frac{x^2}{2})^n \leq (1+x)^n \leq e^{nx} \end{align*} \textbf{1.4} \end{document}